Seroprevalence of Toxoplasma gondii among schizophrenics at Hospital Kajang - Juanah, Lovetta Yatta; Jalaludin, Juliana; Osman, Malina; Jamil @ Osman, Zubaidah (Science Publications, 2013)
Studies have found a high seroprevalence of T. gondii in schizophrenia patients than controls. This case-control study was done to determine the serprevalence of Toxoplasma gondii and to identify its risk factors among schizophrenia patients at Hospital Kajang. Eighty-eight (88) schizophrenia patients and 88 non-psychiatric controls were examined for the presence of anti-Toxoplasma IgG and IgM antibodies by Enzyme Linked Immunosorbent Assay (ELISA). Questionnaires were used to collect socio-demographic and behavioral data among the respondents. From the results, the seroprevalence of anti-T. gondii IgG antibodies was significantly higher (51.0%) in schizophrenia patients than in controls (30.7%); (OR = 2.01; 95% CI: 2.16-3.01; p = 0.023. There was no significant association between the socio-demographic factors and toxoplasmosis. Beef consumption (p = 0.004, OR = 3.852, CI: 1.550-9.569), pork consumption (p<0.001, OR = 13.089, 95%CI: 4.730-36.219) and risky cat contact (p = 0.047, OR = 4.061, 95% CI: 1.985-16.745), were found to be significantly associated with T. gondii infection. Our results show that there is a relationship between toxoplasmosis and schizophrenia.